Peripheral vascular involvement in transthyretin cardiac amyloidosis. A comparative analysis with AL amyloidosis. (14th October 2021) - Stamatelopoulos, K; Delialis, D; Bampatsias, D; Tselegkidi, M E; Petropoulos, I; Theodorakakou, F; Gavriatopoulou, M; Patras, R; Pamboucas, C; Kanakakis, J; Ikonomidis, I; Terpos, E; et al.
Abstract: Background: The pattern of peripheral vascular involvement in the wild type transthyretin-related cardiac amyloidosis (ATTRwt) and its diagnostic utility in differentiating this infiltrating cardiomyopathy from light chain (AL) cardiac amyloidosis (AL-CA) and heart failure with preserved ejection fraction (HFpEF) of different origin have not been explored. Aims: To characterize the pattern of peripheral vascular involvement in ATTRwt and evaluate its value in differentiating ATTRwt from AL-CA and HFpEF. Methods: Newly diagnosed patients with ATTRwt (n=42) were consecutively recruited from our amyloidosis center. These patients were matched 1:1 for age and sex to patients with AL-CA (n=32) and subjects without amyloidosis (n=32) and also matched 2:1 to HFpEF patients (n=16). All subjects underwent a series of non-invasive vascular examinations for the assessment of: 1. subclinical carotid atherosclerosis with B-mode ultrasonography, 2. Arterial stiffness with measurement of carotid-femoral pulse wave velocity, 3. Reactive vasodilation with flow-mediated dilation (FMD) and 4. Aortic blood pressures and arterial wave reflections with augmentation index (AI) and return time of reflected wave (Tr). Results: ATTRwt patients had lower peripheral (pBP) and aortic blood pressure (aBP) markers compared to non-AL controls (p<0.05 for all). ATTRwt grouping was an independent determinant of these markers, after adjustment for cardiovascular risk factors (CVRF), including history of hypertension, hyperlipidemia and diabetes, glomerular filtration rate, body mass index and smoking status (core model). ATTRwt had lower aDBP and increased Tr compared to AL subjects. In a comparison between ATTRwt and AL patients with cardiac involvement, AI and Tr were higher and FMD lower in ATTRwt patients. ATTRwt was an independent determinant of these markers, after adjustment for the core model (p<0.05 for all). Compared to HFpEF, patients with ATTRwt had lower peripheral and central BP and higher Tr (p<0.05 for all). By ROC analysis, Tr provided high diagnostic value for ATTRwt vs. AL-CA (Area Under the Curve, AUC=0.809, CI: 0.65–0.96) and for ATTRwt vs combined AL-CA and HFpEF (AUC=0.880, CI: 0.79–0.97). Finally, AI was closely correlated with posterior (Spearman's Rho=−0.30) and intraventricular wall thickness (Rho=−0.329) and left ventricular global longitudinal strain (Rho=−0.4) and lower cDBP with higher Gilmore and New York Heart Association stage (p<0.05). Conclusion: ATTRwt patients present differential characteristics of peripheral vascular function and aortic hemodynamics as compared to AL, HFpEF and healthy controls. The clinical value of these characteristics merit further investigation since differential diagnosis among amyloidosis types is clinically challenging, while it may have prognostic implications. Funding Acknowledgement: Type of funding sources: None.